Remarks at the UNGA High Level Side Event on Accelerating the End of the COVID-19 Pandemic - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank Group, remarked that the World Bank Group is determined to take action to help people in developing countries gain access to safe vaccines and distribution systems. Economies, families, and livelihoods cannot recover fully until all people are able to work, socialize, travel, and live their lives with hope and confidence. Broad, rapid, and affordable access to COVID vaccines will be at the core of a resilient economic recovery that lifts everyone. The COVID-19 pandemic has caused the steepest economic contraction in 90 years. The Bank estimates that the pandemic could push over 150 million people into extreme poverty by 2021. The negative impact on human capital will be deep and may last decades. During the pandemic, over a billion children have been out of school and 80 million children are missing out on basic childhood vaccinations. This additional financing will be to low- and middle-income developing countries that don’t have adequate access and helping them alter the course of the pandemic for their people. This vaccine financing is additional to the COVID fast-track health financing announced in March and is an important part of the World Bank Group’s intention to make available 160 billion dollars in grants and financial support over a 15-month period to help developing countries respond to the health, social, and economic impacts of COVID-19.